Kernel weight responses to the photo-thermal environment in maize dent × flint and flint × flint hybrids - Hisse, Ignacio R. (2021)
Maize (Zea mays, L.) grain yield is assumed to be source limited during the flowering period but sink limited during grain growth; however, environmental restrictions during active grain filling may strongly affect final kernel weight (KW). In this study we evaluated the effect of natural changes in photo‐thermal conditions during lag phase (LP) and effective grain‐filling period (EGFP) on KW, its physiological determinants, and the post‐flowering source‐sink relationships of flint and semident germplasm. F1 hybrids of flint × flint and dent × flint background were tested during four seasons (Y1, Y2, Y3 and Y4). Across years, the highest KW (286 mg) was obtained under the maximum photo‐thermal quotients during LP (PTQLP: 1.18 MJ m−2 °C−1) and EGFP (PTQEGFP: 1.07 MJ m−2 °C−1) of Y2, whereas the smallest KW (252 mg) and source‐sink ratio during grain filling was obtained under the lowest PTQEGFP (.79 MJ m−2 °C−1) of Y3. Supra‐optimum temperatures during LP of Y3 negatively affected potential KW determination, and hence kernel growth rate (P < .001) as a result of reduced assimilate availability per kernel. Hybrids dent × flint exhibited higher grain yield, kernel number and plant growth around flowering than flint × flint throughout evaluated seasons, but had reduced source‐sink relationship during grain filling (P < .05) and increased KW sensitivity (P < .001) to changes in the photo‐thermal conditions. Results emphasized the importance of the photo‐thermal environment during grain filling on KW determination (particularly for seasons with great photo‐thermal imbalance between filling sub‐phases) as well as the dependency of KW responses on the genetic background.